Scritturalità delle immagini e evoluzione tecnica dei linguaggi. Adieu au langage: Jean-Luc Godard e Jacques Ellul - Coccimiglio, Cristina (Aesthetica Preprint, 2023)
In this paper, I analyze the relationship between word and language from a particular viewpoint – that of the digital and technological revolution of the late 20th and early 21st centuries. In the movie Adieu au Langage, by Jean-Luc Godard, the philosophy of Jacques Ellul – a visionary thinker and a pioneer of political ecology – is expressly cited and honoured. Ellul and Godard express opposing positions regarding the value and function of cinema. On the one hand, Godard shows extreme faith in this art: cinema is for him a tool to think and heal, as well as an instrument for knowing life. As Gilles Deleuze observed about Godard’s style: “it is always (…) a stammering in the language itself”. On the other hand, despite Ellul’s reluctance to undertake a thematic and exclusive reflection on cinema, his position on 20th-century art cannot be defined as reactionary but as consciously provocative. He would attribute that ‘stammering’ to the effect of a crisis that affects first of all the possibility, the sense, and the destiny of the word in the technological system.